1997
DOI: 10.1093/ndt/12.8.1684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haemodynamic variables on surgically created arteriovenous fistula flow

Abstract: The immediate success and flow of a newly constructed arteriovenous fistula is mainly dependent on arterial inflow and subclavian venous flow. An arterial inflow rate of 40 ml/min or more and subclavian venous flow rate of 400 ml/min or more measured by colour flow duplex imaging prior to the operation will be associated with better outcomes, and therefore the use of colour flow duplex imaging is warranted during the evaluation of patients who are candidates for an arteriovenous fistula operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 1 publication
2
54
0
3
Order By: Relevance
“…9 Adequate arterial inflow is critical to the successful maturation of forearm fistulas. Yerdel et al 16 reported that a preoperative arterial flow volume of 40 mL/min or greater was associated with higher postoperative fistula flow rates; however, they were unable to show a linear correlation between the preoperative and postoperative flow rates. Unfortunately, sonographic radial artery flow rate measurement is difficult and poorly reproducible because of the small diameter of the radial artery.…”
Section: Discussionmentioning
confidence: 93%
“…9 Adequate arterial inflow is critical to the successful maturation of forearm fistulas. Yerdel et al 16 reported that a preoperative arterial flow volume of 40 mL/min or greater was associated with higher postoperative fistula flow rates; however, they were unable to show a linear correlation between the preoperative and postoperative flow rates. Unfortunately, sonographic radial artery flow rate measurement is difficult and poorly reproducible because of the small diameter of the radial artery.…”
Section: Discussionmentioning
confidence: 93%
“…The criteria on which a vessel is suitable for AVF creation by duplex ultrasound are not established. Many variables should be considered (89,92,93), and using minimal vessel diameter as a sole criterion should be avoided. Doing so may preclude the use of veins that would have been acceptable by clinical examination (24,94).…”
Section: Continue Fistula First With Review and Reevaluation Of The 1mentioning
confidence: 99%
“…Although mechanisms of AVF maturation are complex and the exact timing of maturation is difficult to pinpoint, ample information exists in the literature regarding the general process (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Nevertheless, the phenomenon remains poorly understood by many nephrologists as well as vascular surgeons.…”
mentioning
confidence: 99%